2014
DOI: 10.1614/wt-d-14-00004.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simulated Indaziflam Drift Rates on Various Plant Species

Abstract: Indaziflam is a PRE herbicide for control of annual grass and broadleaf weeds in numerous settings, including managed roadsides, railroads, and noncroplands. There is a need for new and improved PRE herbicides for herbaceous vegetation management along roadsides; however, off-target crop injury via spray drift is a concern because of the close proximity of roadside applications to the wide array of crops grown throughout the southeastern United States where indaziflam is used. Greenhouse research was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
1
9
0
3
Order By: Relevance
“…ha -1 ), constatouse que as plântulas de beterraba e pepino não emergiram Guerra et al (2014), demonstrando serem espécies importantes na detecção desse herbicida no solo. Já Jeffries et al (2014), simulando deriva após 70 dias depois a aplicação de 1,8 g ha -1 de indaziflam observaram efeitos negativos em plantas de tomate.…”
Section: Revunclassified
See 2 more Smart Citations
“…ha -1 ), constatouse que as plântulas de beterraba e pepino não emergiram Guerra et al (2014), demonstrando serem espécies importantes na detecção desse herbicida no solo. Já Jeffries et al (2014), simulando deriva após 70 dias depois a aplicação de 1,8 g ha -1 de indaziflam observaram efeitos negativos em plantas de tomate.…”
Section: Revunclassified
“…ha -1 ) (Figura 6). Jeffries et al (2014), verificaram reduções na altura das plantas sob simulação de deriva do herbicida indaziflam e que essas reduções foram acompanhadas dos sintomas de fitointoxicação, corroborando os resultados desse trabalho. 3 DAE Y= 100,00/1 + (x/2,62)^0,54 R 2 =0,99 Y= 100,00/1 + (x/2,52)^0,58 R 2 =0,99 Y= 100,00/1 + (x/1,77)^0,69 R 2 =0,99 Y= 100,00/1 + (x/1,69)^0,99R 2 =0,99 3 DAE Y= 100,00/1 + (x/13,83)^2,26 R 2 =0,99 Y= 100,00/1 + (x/9,79)^1,69 R 2 =0,99 Y= 100,00/1 + (x/7,81)^1,53 R 2 =0,99 Y= 100,00/1 + (x/6,28)^1,63 R 2 =0,99 3 DAE Y= 100,00/1 + (x/5,32)^0,95 R 2 =0,98 Y= 100,00/1 + (x/3,17)^1,00 R 2 =0,98 Y= 100,00/1 + (x/0,98)^0,88 R 2 =0,99 Y= 100,00/1 + (x/0,60)^0,85 R 2 =0,99 Figura 6.…”
Section: Revunclassified
See 1 more Smart Citation
“…For cotton, the most sensitive crop, 2.5% of the commercial dose caused a 20% reduction in the root mass (Jeffries et al, 2014).…”
Section: Effects Of the Herbicides Saflufenacil And Indaziflam On Agrmentioning
confidence: 99%
“…Information on the fate and transport behavior of indaziflam is required to minimize off-target plant injury risk (Jeffries et al, 2014). Previous studies reported a decrease of indaziflam injury to bermudagrass with increasing organic matter and clay contents under laboratory conditions (Jones et al, 2013a(Jones et al, , 2013bSchneider et al, 2015).…”
mentioning
confidence: 99%